Oligomeric Structure and Functional Characterization of Caenorhabditis elegans Innexin-6 Gap Junction Protein - Oshima, Atsunori (American Society for Biochemistry and Molecular Biology, 2013)
Innexin is the molecular component of invertebrate gap junctions. Here we successfully expressed and purified Caenorhabditis elegans innexin-6 (INX-6) gap junction channels and characterized the molecular dimensions and channel permeability using electron microscopy (EM) and microinjection of fluorescent dye tracers, respectively. Negative staining and thin-section EM of isolated INX-6 gap junction membranes revealed a loosely packed hexagonal lattice and a greater cross-sectional width than that of connexin26 and connexin43 (Cx43)-GFP. In gel filtration analysis, the elution profile of purified INX-6 channels in dodecyl maltoside solution exhibited a peak at ∼400 kDa that was shifted to ∼800 kDa in octyl glucose neopentyl glycol. We also obtained the class averages of purified INX-6 channels from these peak fractions by single particle analysis. The class average from the ∼800-kDa fraction showed features of the junction form with a longitudinal height of 220 Å, a channel diameter of 110 Å in the absence of detergent micelles, and an extracellular gap space of 60 Å, whereas the class averages from the ∼400-kDa fraction showed diameters of up to 140 Å in the presence of detergent micelles. These findings indicate that the purified INX-6 channels are predominantly hemichannels in dodecyl maltoside and docked junction channels in octyl glucose neopentyl glycol. Dye transfer experiments revealed that the INX-6-GFP-His channels are permeable to 3- and 10-kDa tracers, whereas no significant amounts of these tracers passed through the Cx43-GFP channels. Based on these findings, INX-6 channels have a larger overall structure and greater permeability than connexin channels.